Building Resilient Communities through SME Development: A Qualitative Examination of Management Practices - Putra, Aditya Halim Perdana Kusuma; Ardyan, Elia; Laisila, Maya (Manunggal Halim Jaya, 2025)
This qualitative study investigates the nexus between Small and Medium-sized Enterprises (SMEs) management practices and community resilience. The research aims to explore how effective leadership, strategic management, innovation, sustainable practices, and community engagement contribute to SME resilience and its implications for community well-being. Employing thematic analysis, the study systematically reviews literature on SME management practices and community resilience. Findings reveal that visionary leadership, adaptive management styles, strategic foresight, and risk assessment are pivotal for SME resilience. Innovation, digital transformation, research and development (R&D) investment, and adaptive capacity enhance SMEs' ability to navigate uncertainties and capitalize on opportunities. Moreover, integrating sustainability principles into SME operations mitigates risks, improves financial performance, and fosters community development. Collaboration, knowledge sharing, and community engagement initiatives strengthen SME resilience and contribute to socio-economic development. The study underscores the importance of integrating theoretical insights with practical implications to advance understanding of SME resilience and its role in building resilient communities.